Proceso de Atención de Enfermería en Paciente de 84 años de edad con Insuficiencia Renal Crónica en etapa Terminal. - Cedeño Martínez, Alexis Paul (2020)
This case study is based on a pathology that can occur in various stages but the most fulminant is stage 5 chronic kidney failure or commonly termed as terminal which is characterized by the total loss of kidney function. Which is evidenced by laboratory tests which shows a considerable increase in serum creatinine, the BUN, serum levels. Some studies have shown that the increase in ferritin is due to certain causes such as chronic alcohol consumption and kidney failure. The most common symptoms that are evident in patients with renal insufficiency can be from mild to chronic, in which the increase in blood pressure, nausea, emesis, asthenia, edema predominate. The risk factors that are evident in the studies that lead to this condition are a history of hypertension, diabet mellitus. The current clinical case was performed in an 84-year-old adult male patient with a diagnosis of Terminal Stage Chronic Renal Failure, with a pathological and genetic history of arterial hypertension, which through the nursing diagnosis obtained from the Nanda Taxonomy and interventions From the Nic Taxonomy the improvement of the clinical state that the patient presents was achieved, which shows the efficiency and effectiveness of the Nursing care Process.